Learning at Home: Distance Learning Solutions and Child Development during the COVID-19 Lockdown - Hugues Champeaux; Lucia Mangiavacchi; Francesca Marchetta; Luca Piccoli (Institute of Labor Economics (IZA), 2020)
School closures, forced by the COVID-19 crisis in many countries, impacted on children's lives and their learning process. There will likely be substantial and persistent disparities between families in terms of educational outcomes. Distant learning solutions adopted by schools have been heterogeneous over countries, within countries and between school levels. As a consequence, most of the burden of children's learning fell on their parents, with likely uneven results depending on the socio-economic characteristics of the family. Using a real time survey data collected in April 2020 and early May in France and Italy, we estimate child fixed effects models to analyze how the lockdown has affected children's emotional wellbeing and their home learning process. The analysis also focuses on the role played by online classes or other interactive methods on children's home learning and emotional status. We find that the lockdown had a stronger negative effect on boys, on kids attending kindergarten (in Italy) or secondary school (in France), and on children whose parents have a lower education level. We also find that the increase in the time spent in front of screen is correlated to a worse learning achievement and emotional status, while the opposite is true for the time spent reading. The use of interactive distance learning methodologies, that has been much more common in Italy than in France, appears to significantly attenuate the negative impact on lockdown on the learning progresses of both Italian and French kids.
Keywords: I24; J13; J24; 330; distance learning; education inequality; children's education; children's time-use; emotional skills; COVID-19